Climate, environment and society in the Pacific during the last millennium - Nunn, Patrick D., 1955- (Developments in earth & environmental sciences, 2007)
The nature of global change in the Pacific Basin is poorly known compared to other parts of the world. Climate, Environment, and Society in the Pacific during the Last Millennium describes the climate changes that occurred in the Pacific during the last millennium and discusses how these changes controlled the broad evolution of human societies, typically filtered by the effects of changing sea level and storminess on food availability and interaction. Covering the entire period since AD 750 in the Pacific, this book describes the influences of climate change on environments and societies during the Medieval Warm Period and the Little Ice Age, focusing on the 100-year transition between these - a period of rapid change known as the AD 1300 Event. * Discusses the societal effects of climate and sea-level change, as well as the evidence for externally-driven societal change * Synthsizes how climate change has driven environmental change and societal change in the Pacific Basin * Contains a comprehensive and up-to-date survey of the evidence for climate, environmental, and societal change, supported by a full list of references.